2009
DOI: 10.1371/journal.pone.0006428
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism Enhances Tumor Invasiveness and Metastasis Development

Abstract: BackgroundWhereas there is increasing evidence that loss of expression and/or function of the thyroid hormone receptors (TRs) could result in a selective advantage for tumor development, the relationship between thyroid hormone levels and human cancer is a controversial issue. It has been reported that hypothyroidism might be a possible risk factor for liver and breast cancer in humans, but a lower incidence of breast carcinoma has been also reported in hypothyroid patientsMethodology/Principal FindingsIn this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 49 publications
3
71
0
2
Order By: Relevance
“…It is noteworthy that hypothyroid mice showed higher levels of necrosis in their tumors than the other studied groups, despite having levels of angiogenesis similar to those observed in euthyroid animals. Similar results were obtained by Martínez-Iglesias et al (2009) demonstrating that the reduced tumor volume in hypothyroid hosts was correlated with a lower proliferation rate of the tumors, which was also accompanied by enlargement of the necrotic area …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It is noteworthy that hypothyroid mice showed higher levels of necrosis in their tumors than the other studied groups, despite having levels of angiogenesis similar to those observed in euthyroid animals. Similar results were obtained by Martínez-Iglesias et al (2009) demonstrating that the reduced tumor volume in hypothyroid hosts was correlated with a lower proliferation rate of the tumors, which was also accompanied by enlargement of the necrotic area …”
Section: Discussionsupporting
confidence: 86%
“…Thus, the heterogeneity of the analyzed studies precludes firm conclusions. Martínez-Iglesias et al (2009) showed that hypothyroidism resulted in a decreased rate of solid tumor growth, as well as an increase in the development and number of metastases, in murine xenograft models of human hepatocarcinoma and breast cancer. However, low levels of circulating THs, induced by stress, enhanced tumor progression in mice, an effect that was reversed following T 4 administration (Frick et al 2009a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Group A (euthyroid) was a control with normal drinking water. Group B (hypothyroid) was treated with 0.02% methymazole and 0.1% sodium perchlorate in the drinking water to repress T 3 synthesis (42). Additionally, Group C (hyperthyroid) was added T 3 in the drinking water (2 mg/L) (Sigma Chem.…”
Section: Establishing a Huh7 Cell Line Stably Overexpressing Pai-1-thementioning
confidence: 99%
“…ϩ/ϩ /TR␤ ϩ/ϩ animals with the same background were genotyped (11) and used for the studies. Wild-type mice were made hypothyroid (hT) by treatment with 0.02% methymazole and 0.1% sodium perchlorate in the drinking water (35). Treatment started when animals were 1 month old and was continued for 4 months.…”
mentioning
confidence: 99%